Proteasas de bromeliaceae: I. Estudio preliminar de la fracción proteolíticamente activa presente en frutos de Bromelia laciniosa Mart. - Buttazzoni de Cozzarin, Marta Susana (1984)
Proteolitically active preparations obtained from matute fruits of Brornelia Iaciniosa Mart. were analyzed by molecular sieve chromatography (Sephadex G-75, Superhe). Best resolution and higher activity are achieved by direct trituration of fruits with cold acetone. Proteolytic capacity is notably diminished in case of unripe fruits.